Psychological Support for Students in the Context of Developing Motivation for Pedagogical Activity (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with the issues related to the peculiarities of psychological support of students' professional training. Psychological support of students' professional training is a new direction in psychological science and practice. It is based on the humanisation of relations in society, which requires revision and reassessment of all components of the pedagogical process. In this case, the main meaning of the educational process of the university becomes the development of the student. It is the student's development that should be a measure of the quality of work of a higher education teacher and the whole education system. Formation of professional qualities, knowledge, abilities, skills of the teacher and the student is the basis of the pedagogical process.